Fabrication and optimization of parameters of high-performance polyamide thin film composite membranes for desalination - Muhammad Razzaq; Ajaz Hussain; Sara Musaddiq; Dilshad Hussain; Javaria Kanwal; Saikh Mohammad Wabaidur; Hafiz Muhammad Asif; Muhammad Mahboob Ahmed; Francis Verpoort (Materials Research Express)
Herein, we report the synthesis of polyamide thin film composite (PA-TFC) membranes through interfacial polymerization (IP) using an aqueous solution of diaminodiphenylmethane (DDM) and terephthaloyl chloride (TPC) in n-hexane, onto polysulfone (PSF) surface. The synthesized membranes were characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscope (SEM) and contact angle measurement. To optimize the conditions for better membrane function, desalination (%) and permeate flow rate (L/m ^2 .h.bar) were evaluated as a function of synthesis conditions. The membrane efficiency for salt rejection was evaluated against NaCl using a bench-top cross-flow filtration assembly where the membrane showed up to 73.13% salt rejections of NaCl. While the salt rejection of Na _2 SO _4 and MgSO _4 showed up to 84.92% and 82.94%. The promising synthesized membranes exhibited a permeate flux of 41.7 L/m ^2 .hr.bar. The contact angle analysis revealed that the synthesized PA-TFC membranes are hydrophilic as the value of contact angle measured as 109°–100°. The synthesized membrane offered facile and effective access for the synthesis of high-performance PA-TFC membranes.